ANALISIS SOAL KETERAMPILAN BERPIKIR TINGKAT TINGGI PADA SOAL EVALUASI PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Rina Marlina; Yeni Erita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to describe questions about higher-order thinking skills in the evaluation of Civics lessons used by elementary school teachers. The subjects and objects in this study were class IV teachers and the learning evaluation used by class IV teachers. The research method used is qualitative research. The research instrument used was interviews and documentation. The results of this study indicate that the summative assessment in learning the scope of material one to four as well as the end of semester summative assessment contains questions that focus on low-level thinking skills. With the midterm assessment, there are 28% high-order thinking skills and 72% low-order thinking skills. It can be concluded that only a small part of the learning evaluation used by the teacher contains higher-order thinking skills